Haft manẓūma-yi ḥamāsī : Bīzhān nāmah, Kuk Kūhzād nāmah, Babr-i bayān, Patyārah, Tahmīna nāma-yi kūtāh, Tahmīnah nāma-yi buland, Razm nāma-yi Shakāvandkūh - Ghafūrī, Riḍā, (Miras Maktoob, ISBN: 9789004365452., 2019)
In Persian literary history Firdawsī's (d. 411/1020) Shāh-nāma , the famous masnavi composed in celebration of the history of the kings and dynasties of Persia, is the archetypal epic poem. After the Shāh-nāma , many other epic poems saw the light, among them Asadī Ṭūsī's Garshāsp-nāma (dated 458/1066) and Īrānshāh b. Abi ʼl-Khayr's Bahman-nāma (dated 501/1107-08). There are also Shīʿī adaptations, celebrating the wondrous exploits of ʿAlī b. Abī Ṭālib and the beginnings of Shīʿism, like Rabīʿ's ʿAlī-nāma (dated 482/1089) or Ibn Ḥusām's Khawarān-nāma (completed in 830/1427). The present work unites seven poems around themes inspired by the Shāh-nāma , each of unknown authorship: the Kuk Kūhzād-nama , Dāstān-i Babr-i Bayān , Dāstān-i Patyārah and Razm-nāma-yi Shakāvandkūh , all of the 5-6th/11-12th centuries; the Bīzhān-nāma of the 10th/16th century; and the Tahmīna-nāma-yi kutāh and Tahmīna-nāma-yi buland , not before the 9-10th/15-16th century. The poems each come with an introduction, followed by the text of the work itself. Includes vocabulary and indices.